Taxonomic revision and distribution of Erigeron acris s. l. (Asteraceae) in Poland - Pliszko, Artur (Phytotaxa, 2015)
The species Erigeron acris L. s. l. is revised in Poland. Three subspecies are recognized (E. acris subsp. acris, E. acris subsp. droebachiensis (O.F. Müll.) Arcang., and E. acris subsp. serotinus (Weihe) Greuter), a diagnostic key is provided, syntypes of two synonyms are discovered. Cauline leaves, capitula, and achenes are studied under scanning electron microscope. The updated distribution of the subspecies in Poland are presented using the ATPOL cartogram method. The distribution and hybridization are discussed.